2012
DOI: 10.1111/j.1365-2672.2012.05290.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of class 1 integrons in Salmonella Weltevreden and silent antibiotic resistance genes in some seafood-associated nontyphoidal isolates of Salmonella in south-west coast of India

Abstract: Aims:  To study the antibiogram of 40 seafood isolates of Salmonella and use of PCR to detect the presence of integrons and genes coding for antibiotic resistance. Methods and Results:  In this study, 40 isolates of Salmonella were used for antibiogram analysis. The multidrug‐resistant isolates were analyzed for the presence of integron using integron‐specific primers. Twenty‐five percentage of the isolates were multidrug resistant while 67·50% were resistant to at least two antibiotics. Antibiotic resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 30 publications
9
38
1
Order By: Relevance
“…Thus the present results and those of Deekshit et al. () agree that some antimicrobial‐resistant genes are “silent” in bacteria in vitro; it further provides an indication that these silent genes can spread to other bacteria or turn on in vivo, especially under selection pressure of antibiotic use (Yaqoob et al. ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus the present results and those of Deekshit et al. () agree that some antimicrobial‐resistant genes are “silent” in bacteria in vitro; it further provides an indication that these silent genes can spread to other bacteria or turn on in vivo, especially under selection pressure of antibiotic use (Yaqoob et al. ).…”
Section: Discussionsupporting
confidence: 87%
“…Resistance to traditional antibiotics (AMP, TET, and SUL) was high in Salmonella isolates from animals and foods of animals as observed in this study, previously reported by Deekshit et al. (). It is apparent that resistance to traditional antibiotics such as TETs, AMPs, and cotrimoxazole and detection of their genes in microbial populations of both countries constitute a public health concern by limiting the therapeutic choices for treating salmonellosis in animals and humans.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, approximately 52% of the isolates were resistant to at least one antibiotic, which was higher than other studies in Poland (42.6%; Maka et al, 2015), but lower than figures reported in Tokyo (89.9%; Katoh et al, 2015) and India (67.5%; Deekshit et al, 2012). The overall rate of multi antimicrobial resistance was 36%, which was higher than that described in Korea (29%; Choi et al, 2015) and India (25%; Deekshit et al, 2012), but lower than figures reported in Romania (71.4%; Tirziu et al, 2015), Japan (90.2%; Katoh et al, 2015), and Colombia (98%, Donado-Godoy et al, 2015). The cause of this difference could be attributed to the abuse of antibiotics used in animal feed, used in treatment and prevention of livestock diseases on farms, and use in treatment of human patients, all of which has increased the rate of resistance genes for microorganisms (Miranda, Mondragon, Martinez, Guarddon, & Rodriguez, 2009).…”
Section: Discussioncontrasting
confidence: 73%
“…In wild quinolone resistant isolates (SN36 and SW9), the decreased growth rate, invasion and survival inside the HeLa cell may also be due to other factors such as presence of class 1 integron or their resistance to other antibiotics as reported in a previous study on the same isolates by Deekshit et al . (). Molecular mechanism of how particular mutations in the QRDR region ( gyrA , gyrB , parC and parE ) improve or decrease the growth rate or expression of particular virulence associated genes of SPIs need further study.…”
Section: Discussionmentioning
confidence: 97%